A historical research on the highlights of the 76 years of DZRH: A basis for a radio documentary. - Alfaro, Nicole Angelique M. 4 0 16; 5 (2016)
ABSTRACT This thesis produced a radio documentary recommended for the 76th anniversary of DZRH as a way of commemorating the radio station which was dubbed by the Kapisanan ng Brodkaster ng Pilipinas as the longest running AM radio station in the Philippines. This is a historical study of how DZRH has been for the 76 years, specifically, for the feasibility of this study, after the World War II. This study discussed the milestones of DZRH that made them the longest running AM radio station and its significance to the Filipino People. The researchers conducted interviews with the different personalities of DZRH which included anchors, reporters, operation tulong volunteers, the radio station's administrative staff and its avid listeners. the researchers of this study concentrated on three categories- the radio station's most significant programs, corporate social responsibility and the awards that the radio station has garnered for the past years. It was also stated in the study the significance of DZRH to the Filipino based on the said categories. In addition to that, DZRH's milestones in terms of radio drama, operation tulong and public affairs programming were also identified and was briefly discussed. It was concluded that the most significant DZRH radio programs throughout its 76 years were Gulong ng Palad (1960s), the first radio drama in the Philippines, Operation Tulong (1970s), a programming that discusses the experience of Operation Tulong Volunteers and its beneficiaries, People Power II and DZRH People Power (1980s) which discussed the news, issues and everything about the very historical EDSA II, Liberty in Action, Damdaming Bayan (1990s) which was a news commentary that was hosted by DZRH prominent anchors, Deo Macalma and Joe Taruc, Kasaysayan sa mga Liham kay Tiya Dely (late 1990s) which was very prominent because of the anchor itself, the tagapayo herself, Tiya Dely Magpayo. It was also concluded that the CSR of DZRH revolves around Operation Tulong, a socio-civic organization which aims to promote the spirit of volunteerism to the Filipino People. Aside from the programs and CSRs, it was also included the most significant awards that DZRH has garnered which in this study revealed that it motivates the radio station's employees to work harder to improve their performance and to continue serving with passion and integrity. The paper also took the cognizance of the significance of DZRH as a radio station to the Filipino People for the past 76 years of its existence. On the other hand, the output, Ang Pagbabaliktanaw ni Juan was a reflection of what was researched through table research and interviews about the said topic.
Thesis: (Bachelor of Mass Comnmunication) - Pamantasan ng Lungsod ng Maynila 2016.
Keywords: 2 -- 0; 6; 20; 20; 2